Narcolepsy Severity Scale: a reliable tool assessing symptom severity and consequences. Issue 6 (29th January 2020) - Dauvilliers, Yves; Barateau, Lucie; Lopez, Regis; Rassu, Anna Laura; Chenini, Sofiene; Beziat, Severine; Jaussent, Isabelle
Abstract: Study Objectives: To define clinically relevant Narcolepsy Severity Scale (NSS) score ranges, confirm its main performances and sensitivity to medications, and determine whether items need to be weighted. Methods: One hundred and forty-three consecutive untreated and 238 treated adults with narcolepsy type 1 (NT1) completed the NSS, a 15-item self-administered questionnaire (score: 0–57) that assesses the severity and consequences of the five major narcolepsy symptoms such as daytime sleepiness, cataplexy, hallucinations, sleep paralysis, and disturbed nighttime sleep (DNS). They also completed the Epworth Sleepiness scale (ESS; daytime sleepiness), Beck Depression Inventory (BDI; depressive symptoms), and EQ5D (quality of life). Results: The mean symptom number (4.3 vs 3.5), NSS total score (33.3 ± 9.4 vs 24.3 ± 10.2), and number of narcolepsy symptoms (five symptoms: 53.1% vs 24.8%; four symptoms: 26.6% vs 22.7%; three symptoms: 15.4% vs 32.4%; two symptoms: 4.9% vs 20.2%) were significantly different between untreated and treated patients ( p < 0.0001). DNS was often the third symptom (95.5 per cent). The symptom number was associated with diagnosis delay, age at onset, and ESS and BDI scores. Comparisons with ESS, BDI and EQ5D showed that NSS item weighting was not necessary to highlight between-group differences. Four NSS severity levels were defined (mild, moderate, severe, and very severe) with between-group differences related to treatment. The probability of having ESS ≥ 16, BDI ≥ 20, and EQ-5D < 60 increased with the severity level. Conclusion: NSS is valid, reliable, and responsive to treatment in patients with NT1, with four clinically relevant severity score ranges provided. NSS has adequate clinimetric properties for broadening its use for both clinic and research.